Driving Quality Through People: Strategic Human Resource Management in Indonesian Islamic Schools - Syuhud; Achmad Farid (Universitas Nurul Jadid, 2025)
This study aims to analyze the management of human resource quality improvement at Madrasah Ibtidaiyah Nurul Islam Pasirian Lumajang through the managerial functions of planning, organizing, implementation, and control. Employing a qualitative approach, data were collected via interviews, observations, and documentation. The research focuses on three core programs: Subject Teacher Deliberation (MGMP), training in the development of learning instruments, and training in Islamic Religious Education (PAI) materials. Findings indicate that the principal plays a central role in coordinating these teacher development initiatives in a structured and participatory manner. MGMP facilitates collaborative lesson planning and peer reflection. Training on learning instruments enhances teachers’ administrative and pedagogical readiness to implement the Merdeka Curriculum. The Madrasah Mengaji program integrates religious values into daily educational practices. The study also reveals the need for continuous mentoring and systematic evaluation mechanisms to sustain program effectiveness. The findings imply that integrated human resource management that combines professional capacity-building, religious character development, and institutional leadership can serve as a strategic model for improving educational quality in Islamic primary schools across similar contexts.